Media Design For Ecotourism Promotion In Koanara Village, Ende District - Valentin Romualda Gaudiosa Bella Adur; Yohanes Bastian Vestralen Lameng; Yohana Selvina Wanda (Dinasti Publisher, 2025)
This design aims to design effective and communicative visual communication media to promote ecotourism in Koanara village so that it can introduce several tourist attractions in Koanara village, including Lake Kelimutu, Air Tiga Rasa, Murundao Waterfall, Nuaone Moni and Strawberry Gardens to the wider community. Through this promotional media, it can be a means of increasing tourism promotion to the public / tourists who will visit Koanara Village, Kelimutu District, Ende Regency. The research approach used is the design method, which involves collecting data through interviews, documentation and observation. STP analysis is then applied to the collected data. There are two types of data collected: primary data, which comes from direct sources such as interviews and observations, and secondary data, which is obtained indirectly from sources such as literature reviews and official records.